Mathematical Modelling of Growth Dynamics of Infant Financial Markets - Ronald, Katende (Scientific Research Publishing Inc, 2020)
Developing financial markets are sensitive in many ways. Even some seemingly insignificant factors can impact their growth or failure. In this paper, we examine the major compartments of an infant financial market and the major contributors to the market’s growth using a simple deterministic mathematical model. We find that the impact of single investor on the market is dependent on the rate at which people choose to invest and the rate at which people leave the market due to non investment-related issues.